An Undergraduate Experiment to Verify Cylindrical Wavefront Emission from Light Emitting Diodes - Mishra, P. K.; Chauhan, A. S.; Rustagi, H. V.; Singh, Inderpreet; Arun, P.; Singh, Nimmi; Kumar, Kuldeep (European Journal of Applied Sciences, 2025)
In this work, a simple experiment has been described to study and verify the occurrence of cylindrical wavefront, which are left untouched in the undergraduate levels. The experiment setup comprises of LEDs as the source of light and light dependent resistor (LDR) as the detector. The variation between the light intensity (detected by LDR) as a function of its distance from the LED has been studied. The light intensity at the detector is found to decay as we move away from the LED source. The data points are then fitted to mathematical equations and it is observed that the light decay is not only governed by distance but also by the atmospheric conditions. The equation points to the occurrence of cylindrical wavefront in the emitted light. The same experiment is repeated with three different colored LEDs (red, green and blue) and a similar trend is obtained in all the cases. The work introduces students to concepts rarely mentioned in the text books.